2013
DOI: 10.1021/mp400165b
|View full text |Cite
|
Sign up to set email alerts
|

Hot Melt Extrusion for Amorphous Solid Dispersions: Temperature and Moisture Activated Drug–Polymer Interactions for Enhanced Stability

Abstract: Hot melt extrudates (HMEs) of indomethacin (IND) with Eudragit EPO and Kollidon VA 64 and those of itraconazole (ITZ) with HPMCAS-LF and Kollidon VA 64 were manufactured using a Leistritz twin screw extruder. The milled HMEs were stored at controlled temperature and humidity conditions. The samples were collected after specified time periods for 3 months. The stability of amorphous HMEs was assessed using moisture analysis, thermal evaluation, powder X-ray diffraction, FTIR, HPLC, and dissolution study. In gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 32 publications
0
48
0
1
Order By: Relevance
“…However, more drug loss was observed in SM-SD-SE than in SM-SD-SEDS. This may reflect increased molecular motion within SM-SD-SE, recrystallization of the amorphous drug, and the associated chemical degradation [21,22]. Furthermore, the XRD result for SM-SD-SEDS was similar on day 0 and at 6 months ( Fig.…”
Section: Stabilitymentioning
confidence: 94%
“…However, more drug loss was observed in SM-SD-SE than in SM-SD-SEDS. This may reflect increased molecular motion within SM-SD-SE, recrystallization of the amorphous drug, and the associated chemical degradation [21,22]. Furthermore, the XRD result for SM-SD-SEDS was similar on day 0 and at 6 months ( Fig.…”
Section: Stabilitymentioning
confidence: 94%
“…Therefore, the stability of amorphous drugs has been the subject of many studies. [34][35][36][37][38][39] If the amorphous stability of an API could be predicted early on in the formulation development, it would be possible to conclude if amorphization were a viable route for an API. Nurzynska et al 40 recently developed a predictive model of the amorphous stability of neutral poorly soluble drugs.…”
Section: Mathematical and Statistical Modelsmentioning
confidence: 99%
“…For example, in the Eudragit L system, Carbopol1 974P can be used as a stabilizer (66). Other results have suggested that the Eudragit has the fastest in vitro dissolution pattern because of its high degree of supersaturation among the three PIs (PEG6000, PVP K30 and Eudragit) (67).…”
Section: (1) Formulation Aspectsmentioning
confidence: 99%